2012
DOI: 10.1080/13600834.2012.744223
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone technology and sexual abuse

Abstract: Whilst it is acknowledged that grooming and sexual abuse takes place both in the offline and online environment, the continued convergence of technologies means that the offline and online boundaries are increasingly blurred. This paper will discuss how mobile phone technology can be counterproductive to preventing sexual abuse and can help facilitate sexual offending. The paper will start by giving an overview of what term 'sexual violence' means, and the forms of offending linked to it, as well as its relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Within the academic and public domains, specific attention has been paid to the risks that young people -and in particular adolescent girls -may expose themselves to by engaging in sexting (see for example, Lunceford, 2011). Concerns have tended to focus on the potential for young people to have sexual communication and contact with others (McCartan and McAlister, 2012). This might include sexual harassment, online grooming, sexual pressures and 'objectification via the creation, exchange, collection, ranking and display of images' (Ringrose, Gill, Livingstone & Harvey 2012:8).…”
Section: Sexting Sexual Violence and Exploitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the academic and public domains, specific attention has been paid to the risks that young people -and in particular adolescent girls -may expose themselves to by engaging in sexting (see for example, Lunceford, 2011). Concerns have tended to focus on the potential for young people to have sexual communication and contact with others (McCartan and McAlister, 2012). This might include sexual harassment, online grooming, sexual pressures and 'objectification via the creation, exchange, collection, ranking and display of images' (Ringrose, Gill, Livingstone & Harvey 2012:8).…”
Section: Sexting Sexual Violence and Exploitationmentioning
confidence: 99%
“…The activity thus highlights the increasing intersection between computer technology and human interaction and challenges distinctions between young people's public and private lives and between 'pornography and photography' and 'appropriate and inappropriate sexual intersections' (Hawkes and Dune, 2013: 623). The relative ease with which digital images can be captured and distributed not only makes sexting 'easy' but, according to McCartan and McAlister (2012), may also help to 'neutralise its consequences in the minds of those embarking on it' (2012:264).…”
Section: Media and Sexualitymentioning
confidence: 99%
“…5 Child sexual abusers can use technology to aid them in their sexual abuse, [6][7][8] meaning that a sexual assault can be recorded, stored, altered, and disseminated by email or uploading onto the Internet. 9 The online sexual abuse of youths can be multifaceted, including stalking, grooming, online sexual solicitation, and pornography. 9 There is also evidence that online initiated relationships may progress to face-to-face meetings, resulting in offline sexual contact between the offenders and juvenile victims.…”
Section: Introductionmentioning
confidence: 99%
“…9 The online sexual abuse of youths can be multifaceted, including stalking, grooming, online sexual solicitation, and pornography. 9 There is also evidence that online initiated relationships may progress to face-to-face meetings, resulting in offline sexual contact between the offenders and juvenile victims. 10 Although it is reported that offline sexual abuse of juveniles can be initiated through the Internet, 10 to the authors' knowledge, there is no study concerning the features of sexual abuse that includes the use of digital technology by the offender.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the internet is considered the primary medium for sharing, viewing and distributing indecent images of children (Palmer & Stacey, ). Indecent images found in the collections of offenders range from pictures of clothed and nude children, erotic posing and right to the gross sexual assault of a child (McCartan & McCalister, ). With the use of hi‐tech security systems, internet security programs, computer programs as well as coded/protected internet sites and CSA networks, CSA can acquire, store, manage and protect their child abuse imagery collections with little risk of apprehension (Taylor & Quayle, ; O'Donnell & Milner, ).…”
mentioning
confidence: 99%